2006
DOI: 10.1109/icccn.2006.286292
|View full text |Cite
|
Sign up to set email alerts
|

On Fair and Efficient Power Control in CDMA Wireless Data Networks

Abstract: Abstract-We consider the uplink power control problem in a single cell, multi-user, CDMA wireless data system and formulate it as a cooperative game. We use the Nash bargaining solution concept, in order to determine the socially optimum solution, which is both Pareto efficient and fair. In our formulation, the BS plays the role of the arbitrator, i.e., solves the power control problem, and broadcasts the relevant information to all users in order to enforce convergence to the optimal operating point. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…It has already been shown that the solution to 3 results in a social optimum operating point [1], however we improve on that work by finding the generalized conditions that the solutions must satisfy in addition to an alternative proof of Pareto Optimality.…”
Section: Search For the Optimal Pointmentioning
confidence: 97%
See 2 more Smart Citations
“…It has already been shown that the solution to 3 results in a social optimum operating point [1], however we improve on that work by finding the generalized conditions that the solutions must satisfy in addition to an alternative proof of Pareto Optimality.…”
Section: Search For the Optimal Pointmentioning
confidence: 97%
“…Various algorithms have been considered to reach this operating point, however their convergence depends on various parameters, one of which being the incremental step size of the tax. The authors in [7] presented a possible solution to the problem and while [1] presents a proof of it's optimality, it is directed solely at a very specific modulation. Should the modulation technique or error detection/correction scheme change, the proof is no longer applicable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers maximize over a utility function, where the objective is to have the users achieve an optimal result in a non-centralized manner [1,2,10,11,13,15,19,21,23,24,33,39], while others optimize over a cost function that may be constrained to some target SINR [3,4,9,16]. This is important for media applications as they require a minimum QoS in order to achieve satisfactory performance.…”
Section: Introductionmentioning
confidence: 97%
“…The authors assumed that users should enjoy equal signal-to-interference ratio (SIR) and maximized the user utility function. The resulting operating point is Pareto optimal and fair [17]. However, the authors examined the problem without taking QoS constraints into account.…”
Section: Introductionmentioning
confidence: 99%